2019
DOI: 10.1111/ajt.15400
|View full text |Cite
|
Sign up to set email alerts
|

Clinical importance of the updated Oxford classification in allograft IgA nephropathy

Abstract: With the recent update to the Oxford classification for allograft IgA nephropathy (IgAN), additional investigations on the clinical significance of the updated components are warranted. We performed a retrospective cohort study at two tertiary hospitals. Kidney transplant recipients diagnosed with allograft IgAN were included in the study after additional review by specialized pathologists. We applied the updated Oxford classification and determined the MEST-C scores of the patients. The main study outcome was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 29 publications
1
18
1
1
Order By: Relevance
“…However, given the retrospective nature of the study, only 41 biopsies were tested for C4d and donor-specific antibody status was unknown, thus underestimating the possible role of concurrent acute or chronic antibody-mediated rejection on the pathogenesis of the lesions. Park et al [ 78 ] recently published on the same topic, describing the prognostic importance of the MEST-C classification in a cohort of 333 patients with IgAN in their graft. They found that all the components of the updated IgAN classification system were significantly associated with prognosis.…”
Section: Pathologymentioning
confidence: 99%
“…However, given the retrospective nature of the study, only 41 biopsies were tested for C4d and donor-specific antibody status was unknown, thus underestimating the possible role of concurrent acute or chronic antibody-mediated rejection on the pathogenesis of the lesions. Park et al [ 78 ] recently published on the same topic, describing the prognostic importance of the MEST-C classification in a cohort of 333 patients with IgAN in their graft. They found that all the components of the updated IgAN classification system were significantly associated with prognosis.…”
Section: Pathologymentioning
confidence: 99%
“…Still, it should be noted that the possible benefits of single agent RAASB over single BB or CCB was not confirmed herein for the recurred IgAN cases with confirmed native IgAN. In our previous study, the clinical significance of the Oxford classification was different according to allograft IgAN subtypes [20]. In allograft IgAN with confirmed native IgAN cases, M, E, S, and C components, which may reflect intraglomerular disease activity, were important prognostic parameters, but in the cases without confirmed native IgAN, only the T was a significant pathologic risk factor.…”
Section: Discussionmentioning
confidence: 89%
“…Information on coexisting evidence of acute rejection was also recorded from the pathology reports. Specialized pathologists additionally reviewed the updated Oxford classification, which showed clinical significance also in allograft IgAN [20], in the pathology slides including; M (mesangial hypercellularity), E (endocapillary hypercellularity), S (segmental sclerosis), T (interstitial fibrosis or tubular atrophy), and C (cellular or fibrocellular crescent formation). There were missing cases regarding the Oxford classification because some slides were missing and some were at insufficient quality for additional pathology review.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we aimed to provide supporting evidence for the potential benefits of RAASB in allograft IgAN. We reviewed our retrospective cohort of allograft IgAN patients and identified their prescribed hypertensive medication categories [8,20]. We then compared their prognosis in terms of deathcensored-graft-failure (DCGF) and changes in albuminuria levels.…”
Section: Introductionmentioning
confidence: 99%